Preventive Acupuncture Intervenes Against Cell Proliferation in 7,12-Dimethylbenz(a)Anthracene-Induced Breast Cancer Model Rats Via the PTEN-PI3K/AKT Signaling Pathway - Chunlin Xia, Liwei Xing, Yue Xing, Mei Xu, Chunyan Li, Hongmin Wang, Rong Zhao, Qinzuo Dong, Xiang Li, Yuhuan Sun, Jun Yang, Ying Chen (Forest Chemicals Review, 2021)
Acupuncture as a safe and effective alternative therapy in traditional Chinese medicine (TCM) which has shown unique advantages as well as achieved efficacy in the field of clinical breast cancer prevention. However, there is a lack of experimental evidence regarding the mechanism of action of acupuncture on the process of breast cancer formation. 6-week-old female SD rats were subjected to a single intragastric administration of DMBA at 100mg/kg body weight (BW) to induce spontaneous breast cancer. Preventive acupuncture therapy starting the second week after DMBA administration performed thrice a week for 16 weeks. Tamoxifen (3 mg/kg BW, ig, qd) starting the day right after DMBA administration and lasting for 16 weeks served as a positive control treatment. After treatment, Tumor weight was monitored and immunohistochemical analysis of PI3K/Akt Signaling Pathway-related Proteins and proliferation index of the mammary tumors were performed. Average tumor weight per rat was significantly decreased in PA and tamoxifen treatment groups compared with Model group (P＜0.01). Further immunohistochemical analysis revealed that expression of Ki67 and p-AKT in tumors from rats treated with PA or tamoxifen were significantly lower than those from Model group（P＜0.01）while expression of PTEN in tumors from rats treated with PA or tamoxifen were significantly higher than those from Model group（P＜0.01). Preventive acupuncture therapy can upregulation the expression of PTEN, regulate the PI3K/Akt signaling pathway-related proteins, inhibit the expression of proliferation index Ki67 in mammary tumors, so as to exert an inhibitory effect on DMBA-induced mammary tumorigenesis in female rats.